2010
DOI: 10.1177/0002764210368092
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Comparative Perspective: Policies and Practices

Abstract: This introduction to a pluridisciplinary comparative analysis of European antidiscrimi nation policies and practices provides a critical assessment of current European empirical developments and the analytical issues that they raise. The authors' argument builds upon the tension between the improvement of the protection of rights to equal treatment and the intensification of xenophobia in the European Union. Can proequality policies developed in a hostile context make a difference? The first part of the introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
16
0
3
Order By: Relevance
“…Moreover, severe labour market distractions, such as the economic crisis, make it difficult to recognise discrimination and can weaken the effects of stronger state age discrimination legislation (Neumark and Button 2014). It has also been found that anti-discrimination legislation can raise awareness of the problem among older workers and employers (Amiraux and Guiraudon 2010). However, as noted by Amiraux and Guiraudon (2010), the social fluidity of discrimination contrasts with the boundaries of its legal existence, which calls for more interaction between the two spheres to enhance the efficiency of the legislation and to increase its social impact.…”
Section: Legal Solutions and Responsesmentioning
confidence: 99%
“…Moreover, severe labour market distractions, such as the economic crisis, make it difficult to recognise discrimination and can weaken the effects of stronger state age discrimination legislation (Neumark and Button 2014). It has also been found that anti-discrimination legislation can raise awareness of the problem among older workers and employers (Amiraux and Guiraudon 2010). However, as noted by Amiraux and Guiraudon (2010), the social fluidity of discrimination contrasts with the boundaries of its legal existence, which calls for more interaction between the two spheres to enhance the efficiency of the legislation and to increase its social impact.…”
Section: Legal Solutions and Responsesmentioning
confidence: 99%
“…The long-term effects of functioning of anti-discrimination legislation are still difficult to assess. On the one hand, experts emphasise that such regulations are important for raising awareness to age discrimination among older workers and employers (Amiraux and Guiraudon 2010;Breda and Schoenmaekers 2006). On the other hand, it is assumed that only a small number of age discrimination practices find their way to court, and even if they do, proving guilt is very problematic (Rothenberg and Gardner 2011).…”
Section: Legal and Social Understanding Of Age Discriminationmentioning
confidence: 99%
“…Until 1997, European antidiscrimination policy also occurred primarily at the national level for each country, but this changed significantly with the 1997 Amsterdam Treaty of the European Union. While some protections against discrimination on the basis of nation and gender had been in place previously, the Amsterdam Treaty, along with the European Union (EU) Racial Equality and Employment Framework Directives of 2000 that followed, added new provisions to combat discrimination based on race, ethnicity, religion, disability, age, and sexual orientation (Amiraux and Guiraudon ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while European antidiscrimination policy has made significant gains in recent decades, particularly as it concerns multiple discrimination, several studies find that racism and xenophobia have intensified over the past decade, and that perceptions of discrimination remain high, particularly among Roma populations and immigrants from outside of the EU (Amiraux and Guiraudon ; European Commission ; Zick et al. ) .…”
Section: Introductionmentioning
confidence: 99%